Strategi pengembangan usaha budidaya lobster air tawar di sulawesi selatan - Hamja Abdul Halik (Perbal : Jurnal Pertanian Berkelanjutan, 2015)
The development strategies of Agribusiness-based fresh water lobster Aquaculture in South Sulawesi. The study aims to analyze the strategies in developing agribusiness-based fresh water lobster agriculture in south Sulawesi. This research was conducted in mkassar and Palopo City by using a survey method, Which involved 10 freh water lobster cultivators and stakeholders. The dale wre collected through interviews and observatios and analysis using quantitative. The result reveal the development of agribusiness-based fresh water lobster enterprise pose in south Sulawesi is quadrant II (0,34 ; -0,33). Therefore the comparies are in competitive position. Competitive strategies include the backward, forward and horizontal integration, product development and joint ventures. Some alternative strategie that can be implemented are developing natural action between business runners and optimizing the role of fresh water lobster association in south Sulawesi to develop cooperation among the stakeholders Key words : Strategy, business development, fresh water lobster, agribusiness ABSTRAK